2023
DOI: 10.21037/qims-22-869
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram based on quantitative dynamic contrast-enhanced magnetic resonance imaging, apparent diffusion coefficient, and clinicopathological features for early prediction of pathologic complete response in breast cancer patients receiving neoadjuvant chemotherapy

Abstract: Background:The aim of this study was to develop two nomograms for predicting pathologic complete response (pCR) after neoadjuvant chemotherapy (NACT) for breast cancer based on quantitative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), apparent diffusion coefficient (ADC), and clinicopathological characteristics at two time-points: before and after two cycles of NACT, respectively. Methods: 3.0 T MRI scans were performed before and after 2 cycles of NACT in 215 patients. A total of 74 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Numerous studies have consistently demonstrated that, compared with MG and ultrasound, MRI has superior reliability in monitoring pathological response and evaluating residual tumor size ( 15 - 18 ). Surgeons’ assessment of the tumor relies heavily on post-NAT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have consistently demonstrated that, compared with MG and ultrasound, MRI has superior reliability in monitoring pathological response and evaluating residual tumor size ( 15 - 18 ). Surgeons’ assessment of the tumor relies heavily on post-NAT imaging.…”
Section: Discussionmentioning
confidence: 99%